2014
DOI: 10.4102/td.v10i2.100
|View full text |Cite
|
Sign up to set email alerts
|

The role of musical experience in the lives of Williams syndrome individuals

Abstract: The purpose of this literature study is to better understand the musical experiences of those diagnosed with Williams syndrome. The problem of this study is defined by the lack of qualitative studies done on the musical experiences of Williams syndrome individuals. Research done on music and Williams syndrome emphasise the intense affinity that those diagnosed show towards music listening and music making, yet very few qualitative studies have been done on the importance of musical experience in the everyday l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…According to Biel [ 30 ], individuals with WS expressed frustration with learning in general and said that they wanted to be normal. This notion of struggling to learn is in line with studies by Erasmus [ 5 ] and Erasmus and Van der Merwe [ 6 ] which also found that individuals diagnosed with WS longed to be normal, to be included into their communities and to feel accepted, and that music provided them with such an opportunity. When educating individuals with WS through music, one could provide them with an environment in which they experience less frustration while learning, while also experiencing acceptance from their peers and a sense of belonging [ 29 ].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…According to Biel [ 30 ], individuals with WS expressed frustration with learning in general and said that they wanted to be normal. This notion of struggling to learn is in line with studies by Erasmus [ 5 ] and Erasmus and Van der Merwe [ 6 ] which also found that individuals diagnosed with WS longed to be normal, to be included into their communities and to feel accepted, and that music provided them with such an opportunity. When educating individuals with WS through music, one could provide them with an environment in which they experience less frustration while learning, while also experiencing acceptance from their peers and a sense of belonging [ 29 ].…”
Section: Introductionsupporting
confidence: 79%
“…The affinity that young adults living with WS display toward music [ 15 , 16 , 19 , 20 , 21 , 24 , 46 , 47 , 48 , 49 ], as well as the notion that these individuals could stand to benefit greatly when learning life skills through music [ 5 ], strengthens the argument for the necessity of this study. According to Biel [ 30 ], individuals with WS expressed frustration with learning in general and said that they wanted to be normal.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations